2055. Utility of Aspergillus Galactomannan Assay in Allogeneic Stem Cell Transplant Recipients. (26th November 2018) - Dagher, Sabeen; Medley, Katherine; Haste, Nina; Taplitz, Randy
Abstract: Background: Allogeneic hematopoietic stem cell transplantation (HSCT) is a valuable treatment option for patients with some blood/malignant disorders. However, this procedure may be complicated by life-threatening infections, including invasive aspergillosis (IA). Diagnosis of IA is challenging due to nonspecific symptoms that present similar to other infections; and delays in initiation of treatment are associated with poor outcomes. The galactomannan assay (GM) is a widely used test for the early diagnosis of IA and allows for prompt initiation of antifungal therapy. However, a positive (+) GM result requires further workup for a definitive diagnosis. Furthermore, false-positives can lead to unnecessary treatment with expensive and potentially toxic antifungal medications. At UC San Diego Health, allogeneic HSCT patients not on mold-active agents for antifungal prophylaxis have GM tested weekly until 100 days post-HSCT. This study aims to describe the utility of routine GM assays in this HSCT population. Methods: This is a retrospective single-center study of patients >18 years of age post-allogeneic HSCT at UC San Diego Health from January 2015 to December 2016 with GM results reported in the electronic medical record. Data includes patient demographics, GM results up to 100 days post-HSCT, antifungal prophylaxis, further testing performed, diagnosis of possible, probable and proven IA, and outcome of infection. Results: In total, 108 patients met criteria for enrollment in this study. There were a total of 1, 354 GM results, of which only 2.8% (38) were positive (≥1 +GM) in 25 patients (23% of all patients). Of these, 20 of 25 (80%) were found to be false-positives. In total, 7 of 108 patients had a diagnosis of possible or probable IA. Of the seven, two had 0 +GM, and two had 1 +GM. In the two with 1+GM, IA diagnosis was notably made prior to the +GM result. In only three of the seven cases did +GM screening lead to diagnosis of IA; of these, two patients had acute GVHD and one developed infection during neutropenia, in the first 2 weeks post-HSCT. Conclusion: Routine GM testing adds to cost and is not a useful predictor of IA infection in the studied population. Studies to determine what populations, if any, would most benefit from routine pre-emptive GM or other fungal screening are needed. Disclosures: R. Taplitz, U.C.S.D.: Scientific Advisor, Consulting fee.